Health Counseling About Rheatoid Arthritis In RT 26 Sawah Lebar District, Bengkulu City - Maharani, Nanda; Putri Alessandra, Azelya; Windiah, Nola; Purnamasari, Fita; Lestari, Puja; Marliza, Marliza; Surahman, Fery (Universitas Dehasen Bengkulu, 2024)
Based on data from the World Health Organization (WHO) in 2016, approximately 335 million people worldwide suffer from rheumatism. According to data from the Health Office of Bengkulu City in 2019, based on doctor diagnoses, the prevalence is 11.11%. Gout arthritis is among the top 10 most prevalent diseases in Bengkulu City, ranking 7th (Health Office of Bengkulu City, 2020).The aim of this study is to assess the frequency distribution of knowledge before and after conducting educational activities on rheumatoid arthritis, focusing on improving public understanding as a preventive measure against the disease. The method used in this research involved two activities: lectures and Q&A sessions. Results and Discussion: In this community service activity titled